Ecofisiologia da canola hyola 61 sob variações no arranjo de plantas - Bandeira, Taiane Pettenon (2013)
The adequacy of the spatial arrangement (population and spacing) in canola is extremely important because it constitutes an instrument of management for better utilization of light, water, nutrients and increase the yield of the crop. The aim of this study was to quantify the variation of spatial arrangement on aspects related to the physiology and morphology of the hybrid canola Hyola 61, and its effects on the expression of yield components and grain yield. The experimental design was a randomized block design with split plots, having as main plots, the spacings (17, 34, 51 and 68 cm), and as subplots populations (15, 30, 45 and 60 plants m-2), in two consecutive years (2011 and 2012). The variables evaluated were: plant height, stem diameter, number of leaves, leaf area, leaf area unit, leaf area index, chlorophyll a, b and total in the upper, middle and lower plant fluorescence instant chlorophyll a, quantum yield and photosynthetic light energy in the upper, middle and basal plant, biological yield, straw yield, grain yield and harvest index per plant, number of pods on the primary branch, secondary, tertiary and quaternary , number of pods per plant, number of secondary branches, tertiary and quaternary number of grains per plant, thousand grain weight and grain yield. The variables leaf area index, biological yield per plant, straw yield per plant, number of tertiary and quaternary branches, number of pods in secondary branches, tertiary and quaternary number of grains per plant and number of pods per plant differed significantly as the population factor of crop plants in 2011 and 2012. The appropriate arrangement to obtain maximum yield is 17 cm to 45 plants m-2